Plant Life under Changing Environment Responses and Management - Tripathi D. Phil., Durgesh Kumar; Tripathi D. Phil., Durgesh Kumar; Singh, Vijay Pratap; Chauhan, Devendra Kumar (Academic Press, 2020)
Plant Life under Changing Environment: Responses and Management presents the latest insights, reflecting the significant progress that has been made in understanding plant responses to various changing environmental impacts, as well as strategies for alleviating their adverse effects, including abiotic stresses. Growing from a focus on plants and their ability to respond, adapt, and survive, Plant Life under Changing Environment: Responses and Management addresses options for mitigating those responses to ensure maximum health and growth. Researchers and advanced students in environmental sciences, plant ecophysiology, biochemistry, molecular biology, nano-pollution climate change, and soil pollution will find this an important foundational resource. - Covers both responses and adaptation of plants to altered environmental states - Illustrates the current impact of climate change on plant productivity, along with mitigation strategies - Includes transcriptomic, proteomic, metabolomic and ionomic approaches